Ciência e educação na década de 1950: uma reflexão com a metáfora percurso - Marcus Cunha Vinicius da (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Situates the relevance of the Brazilian and Regional Centres of Educational Research for the emergence of the debate concerning the meaning of scientific research in the educational field which allowed a significant discussion to flourish on the concept of educational research and on the definition of science in this field. It analyses the declarations of Anísio Teixeira and Florestan Fernandes as representatives of two conceptions with regard to the links between science and education, making use of rhetorical analysis and giving particular emphasis to the metaphor trajectory. This metaphor admits two connotations: determinate trajectory and indeterminate trajectory. When analysing Anísio Teixeiras ideas and those of other authors linked to the Brazilian Centre influenced by the ideas of John Dewey, this study locates them as components of the indeterminate trajectory metaphor which has its origin in Deweys conception of science inspired in the theoretical developments of quantum physics.